Enhancing Performance of 1-aminopyrene Light-Emitting Diodes via Hybridization with ZnO Quantum Dots - Jonghyun Choi; Kim, Hong Hee; CHOI, WON KOOK (한국센서학회, 2022)
In this study, a pyrene-core single molecule with amino (-NH2) functional group material was hybridized using ZnO quantum dots (QDs). The suppressed performance of the 1-aminopyrene (1-PyNH2) single molecule as an emissive layer (EML) in light-emittingdiodes (LEDs) was exploited by adopting the ZnO@1-PyNH2 core？shell structure. Unlike pristine 1-PyNH2 molecules, the ZnO@1- PyNH2 hybrid QDs formed energy proximity levels that enabled charge transfer. This result can be interpreted as an improvement insurface roughness. The uniform and homogeneous EML alleviates dark-spot degradation. Moreover, LEDs with the ITO/PEDOT:PSS/TFB/EML/TPBi/LiF/Al configuration were fabricated to evaluate the performance of two emissive materials, where pristine-1-PyNH2molecules and ZnO@1-PyNH2 QDs were used as the EML materials to verify the improvement in electrical characteristics. The ZnO@1-PyNH2 LEDs exhibited blue luminescence at 443 nm (FWHM = 49 nm), with a turn-on voltage of 4 V, maximum luminance of 1500 cd/m2 , maximum luminous efficiency of 0.66 cd/A, and power efficiency of 0.41 lm/W.